Pedicle First Anterior Approach to Harvest Anterolateral Thigh Flap—Review of 304 Cases - G.S. Kalra; Samarth Gupta; Sushrut Kalra (Indian Journal of Plastic Surgery)
Background Although considered as a workhorse flap, the anterolateral thigh (ALT) flap has a steep learning curve that makes it difficult for microsurgeons to perform it early in their practice. In over 85% of patients, the perforator takes an intramuscular course making it difficult for beginners to safely secure the perforator dissection. In this technique, the pedicle is dissected first, utilizing the proximal incision by palpating the groove in between vastus lateralis and rectus femoris on the anterior aspect and extending the incision from 2 to 3 cm distal to the inguinal ligament to the flap markings caudally. Exposing the pedicle first makes it easier to proceed toward the skin perforator due to its easy identification and larger size at its origin. Patients and Methods This retrospective study was conducted from 2005 to 2020 in which 304 ALT flaps were performed by the pedicle first technique. Flap harvest time, incidence of injury to the skin perforator during harvest, flap re-exploration rates, and postoperative complications including incidence of flap necrosis, infection, and bleeding were the parameters that were measured. Results This study included a total of 304 patients of which 220 were male (72.3%). The average flap harvest time was 26 ± 3.2 minutes. Adverse events included perforator injury (n = 1), flap re-exploration (n = 15), and complete flap loss (n = 8). The last eight patients were reconstructed secondarily with ALT flap from the opposite side and free latissimus dorsi flap (n = 2). Conclusion The pedicle first technique makes ALT flap harvest easy, safe, and faster for plastic surgeons. The chances of injury to the skin perforator are markedly less thereby reducing postoperative complications.